Workshop Pelatihan Simulasi Wokwi dan Implementasi Modul Starter IoT untuk Meningkatkan Kompetensi Siswa SMK NADA - Rini Puji Astutik; Denny Irawan; Arbi Alfian Mas'ud; Muhammad Ramadhani; Samsudin Nur (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2026)
SMK Nasional Dawarblandong (SMK NADA) is a vocational school that focuses on developing technological skills; however, it still faces limitations in practical learning facilities, particularly in the field of Internet of Things (IoT). Preliminary observations showed that 78% of students had never used microcontroller devices and 85% had never used IoT simulation platforms such as Wokwi. This condition contributes to low levels of technical competence among students, while industry demand for IoT-related skills continues to increase. This community service program aimed to improve students' competencies through a training workshop on Wokwi simulation and the implementation of an IoT starter module using Arduino and ESP32. The training applied a participatory learning approach consisting of theoretical explanation, simulation practice, case studies, and direct hardware implementation. The evaluation was conducted using pre-test, post-test, and participant satisfaction questionnaires. The results indicated a significant improvement in students’ understanding of IoT concepts and automation systems. Questionnaire analysis showed that 36% of participants rated the clarity of tutor explanations with the highest score (score 5), indicating excellent communication effectiveness during training. Overall, the training successfully improved students' knowledge and practical skills in IoT simulation and microcontroller-based automation systems.